2004
DOI: 10.1023/b:sola.0000022977.95023.a7
|View full text |Cite
|
Sign up to set email alerts
|

The North–South Asymmetry of Soft X-RAY Flare Index During Solar Cycles 21, 22 and 23

Abstract: In this paper the N−S asymmetry of the soft X-ray flare index (F ISXR) during the solar cycles 21, 22 and 23 has been analyzed. The results show the existence of a real N−S asymmetry which is strengthened during solar minimum. The slope of the regression lines fitted to the daily values of asymmetry time series has been found to be negative in all the three cycles. The yearly asymmetry curve can be fitted by a sinusoidal function with a period of eleven years. The power spectral analysis of daily asymmetry tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…In 1997, 1999 and 2000, when the cycle was in ascending phase, northern hemisphere dominated. The preference for northern hemisphere during the rising and maximum phase of cycle 23 is reported by Ataç andÖzgüç (2001) and Joshi and Joshi (2004) (2001) we find that the variations in N-S asymmetry index during cycle 23 differ from cycle 22 but are similar to cycle 21. There was mostly a southern dominance during cycle 22 while cycle 21 showed northern dominance during the early phases and southern dominance during the later phases.…”
Section: Latitudinal Distribution and N-s Asymmetrysupporting
confidence: 77%
See 1 more Smart Citation
“…In 1997, 1999 and 2000, when the cycle was in ascending phase, northern hemisphere dominated. The preference for northern hemisphere during the rising and maximum phase of cycle 23 is reported by Ataç andÖzgüç (2001) and Joshi and Joshi (2004) (2001) we find that the variations in N-S asymmetry index during cycle 23 differ from cycle 22 but are similar to cycle 21. There was mostly a southern dominance during cycle 22 while cycle 21 showed northern dominance during the early phases and southern dominance during the later phases.…”
Section: Latitudinal Distribution and N-s Asymmetrysupporting
confidence: 77%
“…There is a strong southern dominance during the solar cycle minima in 1996. This behavior of asymmetry that it peaks at or around the minimum phase of solar activity has been reported in several studies with different manifestations of solar activity (Swinson, Koyama, and Saito 1986;Vizoso and Ballester 1990;Joshi and Joshi 2004). In 1997, 1999 and 2000, when the cycle was in ascending phase, northern hemisphere dominated.…”
Section: Latitudinal Distribution and N-s Asymmetrysupporting
confidence: 76%
“…For certain solar cycles there may be evidence that the N-S asymmetry evolves with the solar cycle, whereas in general this is not the case. By studying the north-south asymmetry of soft X-ray flare index in cycles 21-23, Joshi & Joshi (2004) found that there exists a real north-south asymmetry in solar flare activity which is not due to random fluctuations, and the hemispheric asymmetry is strengthened during solar minimum. They also found that the hemispheric asymmetry of soft X-ray flare index has a periodic behavior shifted in phase with respect to the solar cycle, and the significant periods of daily asymmetry time series are around 28.26 days, 550.73 days and 3.72 years.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that there are many differences between northern and southern hemispheres in individual cycles. There has been much interest for many years in describing and understanding such differences (Verma, 1993;Oliver and Ballester, 1994) for solar flares (Garcia, 1990;Joshi and Joshi, 2004), the solar wind (Mursula and Zieger, 2001;Bzowski et al, 2003), long-lived solar filaments (Duchlev, 2001), solar and heliospheric magnetic fields (Bravo and Gonzáles-Esparza, 2000), cosmic-ray propagation (Simpson, Zhang, and Bame, 1996), and geomagnetic activity (Murayama and Nosaka, 1991).…”
Section: Introductionmentioning
confidence: 99%